The Effect of Leverage, Liquidity and Profitability on Financial Distress with the Effectiveness of the Audit Committee as a Moderating Variable - Saputri, Lilis; Asrori, Asrori (Accounting Analysis Journal, 2019)
This study aims to analyze and describe the effect of variable leverage, liquidity, and profitability on financial distress with the addition of moderating variables, the effectiveness of audit committee. Mining companies listed on the Stock Exchange in 2013-2016 are the population in this study, which consisted of 48 companies each year. The purposive sampling method is used to select the sample so that there are 80 analysis units from 20 companies. The data analysis technique in this research used moderating regression analysis with IBM SPSS for windows version 21.0. The result of this research showed that leverage, liquidity, and profitability have no significant effect on financial distress. Effectiveness of audit committee has proven to be a moderating variable between the variables of leverage and profitability of financial distress, but cannot be a moderating variable between the variables of liquidity and financial distress. The conclusion of this research is control from audit committee to the management company will improve management performance so it will avoid the company from possible happening of financial distress.